Semiotics of Prohibited Ornaments (Awisan) in Tamanan Ward - Sri Wahyuning Septarina; Eko Wahyu Sentavito (Borong Newinera Publisher, 2023)
Tamanan Ward is a relic building of the Majapahit kingdom era located in the Keraton Yogyakarta area. The existence of Tamanan Ward is supported by physical evidence, such as the sengkalan in the form of Bethara Gana or Ganesha found at the entrance of the ward and resembles Kori Agung. The Tamanan Ward building is historical evidence of cultural acculturation and depiction of royal heritage from time to time as shown by its ornaments. The ornaments in this building include: Praban motif ornaments and Putri Merong motif ornaments which are referred to as prohibited ornaments (awisan). The awisan ornament is a manifestation of the Sultan's power to organize and build palace buildings that have a broad philosophical meaning. Based on this, the two ornaments that decorate the palace buildings have aesthetic and semiotic functions as a marker. This research aims to explain the meaning and philosophy attached to awisan ornaments in Tamanan Ward through a semiotic approach. The research method used was descriptive qualitative method with data collection technique in the form of literature study through relevant books and journals. The results of this study indicated that, first, the building ornaments of Tamanan Ward were influenced by the visual identity that was present due to the power of the Sultan as King, Second, the analysis of the meaning and function of awisan ornaments can be described using a semiotic approach. Third, the Keraton Yogyakarta building is one of Indonesia's cultural assets and its existence needs to be maintained and preserved.